Characteristic analysis of layered PMSEs measured with different elevation angles at VHF based on an experimental case. Issue 1 (29th March 2021) - Ge, ShuCan; Li, HaiLong; Xu, Bin; Xu, Tong; Meng, Lin; Wang, MaoYan; Hannachi, Abdel; Zhu, MengYan; Broman, Lina; Ullah, Safi; Rauf, Abdur
Abstract: Polar Mesosphere Summer Echoes (PMSEs) are very strong radar echoes observed at altitudes near the polar summer mesopause. One of the essential properties of these radar echoes is that they can give useful diagnostic information about the physics of the scattering process. In this paper, the related characteristics of PMSEs measured with the European Incoherent SCATter Very High Frequency (EISCAT VHF) 224 MHz radar on 13–15 July 2010 are studied at different elevation angles from 78° to 90°. It is found that the PMSEs peak power and strongest PMSEs average power occur at the same elevation angles. Also interesting is that the strongest PMSEs occur at off‐vertical angles when a PMSEs has a layered (multilayer) structure. And reflection may have more significant effects on PMSEs when there are double or multilayer PMSEs. Possible explanations regarding these observations are discussed. Key Points: The PMSEs peak power and strongest PMSEs average power occur at the same elevation angles. The strongest echoes occur at off‐vertical elevation angle when there is layered PMSEs. Anisotropic scattering theory maybe dominates the layered PMSEs.